(3GdELgGO GdhGdOj ceJZjQ hSjW Hjf GdCOGA GdhXjaj GdCSQj hGdeTcdGJ GdSdhcjI dOj GdCWaGd Phj GVWQGH bUhQ GdGfJHGg hGdfTGW GdRGFO (B/s - (3,CeGfj fGUQ YHOGddg Ydjs; (3YeQh QeVGf YWGjGs; (3ESQGA NGdO eMeO LeGd GdOjfs (2024)
(3gOaJ GdOQGSI Edj GdJYQa Ydj GdOhQ GdhSjW ddELgGO GdhGdOj Hjf GdCOGA GdhXjaj GdCSQj hGdeTcdGJ GdSdhcjI dOj CWaGd bUhQ GdGfJHGg hGdfTGW GdPGFO , JchfJ YjfI GdOQGSI ef (B(150) (3CekG ef CegGJ CWaGd bUhQ GdGfJHGg hGdfTGW GdPGFO JQGhMJ CYeGQgf GdRefjI Hjf (B(25- 45) (3ceG JQGhMJ CYeGQ CWaGdgf Hjf (B(7-9) (3SfhGJ , hJeKdJ COhGJ GdOQGSI aj ebjGS GdELgGO GdhGdOj efGd YHOGdfYje(B( 2021 )(3, ebjGS GdCOGA GdhXjaj GdCSQj EYOGO GdHGMKI, ebjGS GdeTcdGJ GdSdhcjI EYOGO GdHGMKI, (B((3ebjGS chfQR dJbje Sdhc GdWad(B)(3, hbO JhUdJ fJGFL GdOQGSI Edj Cf eJZjQ GdELgGO GdhGdOj jJhSW GdYdGbI Hjf GdCOGA GdhXjaj GdCSQj hGdeTcdGJ GdSdhcjI; MjK GfNaVJ bjeI eYGed GdGQJHGW GdSGdH Hjf GdCOGA GdhXjaj GdCSQj hGdeTcdGJ GdSdhcjI; eeG jTjQ Edi hLhO OhQ hSjW (B((3hSGWI cdjI(B) (3ddELgGO GdhGdOj (B.s
The study aimes to identify the mediating role of parental stress between family functional performance and behavioral problems among children with hyperactivity and attention deficit disorder(3, (Bsample consisted of (150) mothers of children with hyperactivity and attention deficit disorder, whose chronological ages ranged between (25-45), and the study tools were In the Parental Stress Scale, Manal Abdel Naeem (2021), the Family Functional Performance Scale prepared by the researcher, the Behavioral Problems Scale prepared by the researcher, (Conners Scale for Assessing Child Behavior). The results of the study concluded that the parental stress variable mediates the statistically significant relationship between family functioning and problems. behavioral; The value of the negative correlation coefficient between family functioning and behavioral problems decreased. Which indicates a mediating role (total mediation) for parental stress.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B120-140.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJQHjI GdNGUIs; (3GVWQGH aQW GdMQcI hfbU GdGfJHGgs -- (3GdELgGO GdhGdOjs -- (3GdCOGA GdhXjaj GdCSQjs